METHODICAL APPROACH TO DEFINING INFRASTRUCTURE COMPONENT OF THE COSTS FOR THE PARTICULAR PASSENGER TRAIN TRAFFIC - Barash, Yu. S.; Kravchenko, Kh. V.; Zianchuk, M. F. (Science and Transport Progress, 2015)
Purpose. In the scientific paper a methodical approach concerning determining the infrastructure component of the costs for traffic of the particular passenger train should be developed. It takes into account the individual characteristics of the particular train traffic. Methodology. To achieve the research purposes was used a method which is based on apportionment of expenses for the traffic of a particular passenger train taking into account the factors affecting the magnitude of costs. This methodology allows allocating properly infrastructure costs for a particular train and, consequently, to determine the accurate profitability of each train. Findings. All expenditures relating to passenger traffic of a long distance were allocated from first cost of passenger and freight traffic. These costs are divided into four components. Three groups of expenses were allocated in infrastructure component, which are calculated according to the certain principle taking into account the individual characteristics of the particular train traffic. Originality. The allocation method of all passenger transportation costs of all Ukrzaliznytsia departments for a particular passenger train was improved. It is based on principles of general indicators formation of each department costs, which correspond to the main influential factors of operating trains. The methodical approach to determining the cost of infrastructure component is improved, which takes into account the effect of the speed and weight of a passenger train on the wear of the railway track superstructure and contact network. All this allows allocating to reasonably the costs of particular passenger train traffic and to determine its profitability. Practical value. Implementing these methods allows calculating the real, economically justified costs of a particular train that will correctly determine the profitability of a particular passenger train and on this basis it allows to make management decisions on amendments to the existing schedule. Also, the cost of using the infrastructure for a particular train and its profitability can be determined with the help of PC due to this method.